Proteomics analysis of body fluid exosomes of rheumatoid arthritis patients underwent oxhorn cupping therapy. - Du Leng; Chimedragchaa Chimedtseren; Tegexibaiyin Wang; Ruga Su; Saren Bao; Xiele Mo; Xigesaiyin Ge; Suna Cha; Runtulaguer Xi; Saqila Wu; RenGaoWa Sa; Jiaqi Zhao; et al. (PLoS ONE)
Objective The present study was undertaken to understand the multitarget mechanisms of oxhorn cupping therapy (OHCT) in treating rheumatoid arthritis by proteomic analysis. Methods Thirty rheumatoid arthritis patients underwent OHCT and liquid (body fluid) accumulated in the cupping vessels was collected. Exosomes from the body fluid were isolated and characterized by transmission electron microscope (TEM). Particle size analysis, fluorescent labeling, and flow cytometry detection were also performed. Label-free quantitative proteomics analysis was used to detect differentially expressed proteins (DEPs). The Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment, gene ontology (GO) enrichment, clusters of orthologous groups (COG), and protein-protein interaction (PPI) network were used to perform bioinformatics analysis of DEPs. Enzyme-linked immunosorbent assay (ELISA) was used to detect the key targets regulated by OHCT. Results According to TEM images, the average size of exosomes in body fluid of RA patients underwent OHCT was 76.13 nm (5.27E+10 /mL). The positive rates of CD9, CD63, and CD8 were detected on the surface of body fluid exosomes. A total of 300 DEPs (58 up-regulated and 242 down-regulated) were identified between the pre-treatment and post-treatment stages. DEPs were related mostly to protein binding, focal adhesion, extracellular region, post-translational modification and signal transduction. KEGG pathway analysis showed a significant enrichment of DEPs in PI3K-Akt pathway and focal adhesion. Ten DEGs (ITGA5, ITGA4, ENG, MMP14, SERPINH1, THY1, TAGLN, ITGA1, IGF1, and ITGB5) were considered target genes according to PPI network analysis. ELISA showed a slight decrease in the serum levels of CDK1, ITGA5, ITGB5, and CD44 during and after treatment. Conclusions Body fluid samples from RA patients treated with oxhorn cupping contain exosomes. OHCT might exert therapeutic effects in RA through multiple signaling pathways and multiple protein targets.